Chile Earthquake Of 2010 : Assessment of Industrial Facilities Around Concepci on. - Soules, J. G.; Bachman, Robert E.; Silva, John F. (Reston : American Society of Civil Engineers, 2016)
This report contains the findings of an engineering team that assessed the effects of the 2010 Chile earthquake and tsunami on industrial facilities near Concepci on.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Earthquake resistant design - Standards - Chile; Electronic books